The Influence of Services Quality and Customer Trust on Customer Satisfaction of PT Bumi Daya Plaza at PT PAL Indonesia - Pravanga Agustin Iriani; Muhammad Anang Firmansyah; Muhammad Alhakim Danurwindo (P3I UMSurabaya, 2025)
An effect of product quality, brand image, and price perception on the purchase decision of Clorismen skincare products in Surabaya through the Shopee marketplace had been analysed in this research. This quantitative research used a purposive sampling technique involving 138 respondents using Clorismen. The data collected through the questionnaire were analyzed using multiple linear regression with SPSS version 26. The results showed that product quality (significance 0.000), brand image (significance 0.001), and price perception (significance 0.002) partially had a positive and significant effect on purchase decisions. Simultaneously, these three variables also had a significant effect on the purchase decision (significance 0.000 with a determination coefficient (R²) of 0.512. It indicated that 51.2% of the variation in purchasing decisions can be explained by product quality, brand image, and price perception.